1983
DOI: 10.1002/j.1460-2075.1983.tb01611.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of vertebrate gap junction protein.

Abstract: A new method for the purification of gap junctions is described which depends on the extraction of cell monolayers or tissue homogenates with Triton X-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…While many lines of evidence, notably the recovery of GJIC after transfection of connexin genes into GJIC-de®cient cells, indicate that connexins are an essential component of gap junctions, it remains impossible to exclude a role of the 16 K protein in GJIC. Evidence supporting such a role includes the fact that the 16 K protein apparently constitutes the major protein component of gap junction channels of arthropods, which do not appear to contain connexin homologs (Finbow et al, 1983;1984).…”
Section: Introductionmentioning
confidence: 99%
“…While many lines of evidence, notably the recovery of GJIC after transfection of connexin genes into GJIC-de®cient cells, indicate that connexins are an essential component of gap junctions, it remains impossible to exclude a role of the 16 K protein in GJIC. Evidence supporting such a role includes the fact that the 16 K protein apparently constitutes the major protein component of gap junction channels of arthropods, which do not appear to contain connexin homologs (Finbow et al, 1983;1984).…”
Section: Introductionmentioning
confidence: 99%
“…A new method of isolating gap junctions has recently been developed in this laboratory which allows the preparation of gap junction enriched fractions from various tissues and from cultured cells (Finbow et al, 1983). Using this method we have found that a single major protein, mol.…”
Section: Introductionmentioning
confidence: 99%
“…wt. 16 000 (16 K), is associated with gap junction preparations from a variety of vertebrate tissues and cultured cells (Finbow et al, 1983). This method has now been applied to the preparation of gap junctions from arthropod tissues.…”
Section: Introductionmentioning
confidence: 99%
“…TPA, on metabolic cooperation have shown a positive correlation between the efficacy of the agent as a tumor promoter and the severity of the decrease in cooperation (79). In at least one of these systems, V79 cells treated with TPA, there is a decrease in gap junctions and in the amount of a putative junctional protein (18,78); in another system there is a demonstrable decrease in electrical coupling (14). The time required for these junctional responses to develop is appreciable (1 or 2 days), so that the relationship between TPA treatment and the junctional response involves a number of unknown mechanisms (44).…”
Section: Modulation Of Junctional Capacitymentioning
confidence: 99%